2015
DOI: 10.14393/bj-v31n6a2015-26340
|View full text |Cite
|
Sign up to set email alerts
|

Milk quality of properties with different technological standards

Abstract: ABSTRACT:This study aimed to assess the parameters of milk quality of properties with different technological standards. Twenty five properties were analyzed from 7 countries from the West of Santa Catarina, and classified according to production technologies (feeding, breeding and management practices in general), capital used in the activity, technological standard of machinery, equipment and infrastructure. Ten properties were classified as low technological standard, 8 intermediate standard and 7 high tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…Freitas et al (2017) found higher percentage of fat and SCC in animals with lower milk yield (5-15 kg day) when compared to the group of higher productivity (over 30 kg day -1 ). Similar results were also found by Roza et al (2015) when comparing properties with a low technological standard compared to medium-and high-technology groups.…”
Section: Figure 2 -Triplot Of Response Variables (Prot Fat Lact Scsupporting
confidence: 81%
“…Freitas et al (2017) found higher percentage of fat and SCC in animals with lower milk yield (5-15 kg day) when compared to the group of higher productivity (over 30 kg day -1 ). Similar results were also found by Roza et al (2015) when comparing properties with a low technological standard compared to medium-and high-technology groups.…”
Section: Figure 2 -Triplot Of Response Variables (Prot Fat Lact Scsupporting
confidence: 81%
“…A SCC below 100,000 cells/ml is currently set as the physiological limit [8]. The main factor that affects the somatic cell count (SCC) is the presence of infection in the mammary gland (mastitis) that occurs by the invasion of microorganisms, which results in the increase of the animal defence cells (somatic cells) in the milk [9].…”
Section: Introductionmentioning
confidence: 99%
“…A maioria das fazendas produtoras de leite no Brasil apresentam algumas características em comum como baixa produção de leite por vaca, baixa qualidade do leite e baixo retorno econômico-financeiro (PAIXÃO et al, 2015;PICOLI et al, 2015;ROZA et al, 2015;NASCIMENTO et al, 2012). Uma das possíveis explicações para esta realidade pode estar no fato de que os produtores rurais não enxergam a fazenda como um negócio, ou ainda, que o produtor de leite não vê a sua propriedade como uma empresa.…”
Section: Introductionunclassified